Audit Committee Characteristics and Financial Performance: Indonesian Evidence - Ashari, Sidiq; Krismiaji, Krismiaji (EQUITY, 2019)
This research investigates the effect of audit committee characteristics, which includes independence (ACIN), size (ACSIZE), competence (ACCO), and frequency of meetings (ACMT) on the financial performance (PERF) of manufacturing firms listed on the Indonesian Stock Exchange for the year of 2016 and 2017. PERF is measured and proxy with the return on assets (ROA); ACIN is measured by the percentage of members from outside the company; ACCO is measured using percentage of audit committee members who have accounting and finance educational background; and ACMT is measured using the number of audit committee meetings in 2016 and 2017. The study finds that all of the characteristics of audit committee positively affect the company's performance. The research also uses three control variables, which are the quality of auditors (BIG4), financial leverage (LEV) and company size (SIZE). BIG4 and LEV positively affect the company's financial performance, while the financial performance of the company is negatively affected by SIZE.